Systematic palaeontology of the Perisphinctoidea in the Jurassic/Cretaceous boundary interval at Le Chouet (Drôme, France), and its implications for biostratigraphy - Frau, Camille; Bulot, Luc G.; Wimbledon, William A. P.; Ifrim, Christina (Acta geologica Polonica, 2016)
This study describes ammonite taxa of the Perisphinctoidea in the Jurassic/Cretaceous boundary interval at Le Chouet (Drôme, France). Emphasis is placed on new and poorly known Himalayitidae, Neocomitidae and Olcostephanidae from the lower part of the Jacobi Zone auctorum. Significant results relate the introduction of Lopeziceras gen. nov., grouping himalayitid-like forms with two rows of tubercles, and Praedalmasiceras gen. nov., grouping the early Berriasian Dalmasiceras taxa. Study of the ontogenetic sequences of both genera show that they were derived from late Tithonian Himalayitidae. This supports the distinction between the subfamilies Himalayitinae and Dalmasiceratidae subfam. nov. Content, variation, dimorphism and vertical range of the Neocomitidae Berriasella, Pseudoneocomites, Elenaella and Delphinella are discussed. A conservative use of the Olcostephanidae Proniceras is followed herein.
Gesehen am 25.05.2020
DOI funktioniert nicht